Detection of fungi in fabric toys for immunocompromised children: an experimental study - Magalhães, Beatriz Sordi; Almeida, Tiago Tognolli de; Marques, Letícia Maria Acioli; Castro, Liz Eduarda Leite de; Roel, Antonia Railda; Oliveira, Carina Elisei de; Almeida, Rodrigo Guimarães dos Santos; Marcheti, Maria Angélica; Espinola Carvalho, Cristiano Marcelo; Marques, Fernanda Ribeiro Baptista (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Immunosuppression may occur as an adverse reaction to chemotherapy treatment. Thus, neutropenia makes children with cancer susceptible to infectious conditions. In this context, fabric toys bring comfort and coziness, are malleable, and pose no risk of injury, but they can be considered a focus of pathogenic microorganisms. Aim: Identifying fungal microorganisms in fabric toys used by patients undergoing cancer treatment. Outlining: Samples were collected using swabs soaked in Potato Dextrose (PD) medium directly from the surface of fabric toys, plush toys (B1), and comfort objects (B2), which circulate in hospital and domestic environments of children with oncological diseases. Analysis occurred through molecular identification, conducted by DNA extraction. Results: Six (6) fungal isolates of B1 from the genus Trichoderma and two (2) fungal isolates of B2 from the species Aspergillus niger were obtained. Implications: The method used allowed identifying fungal microorganisms present in toys at the genus and species level, reinforcing the idea of finding sanitizers or means to promote safe disinfection of plush toys brought from home to prevent their transmission.